PENERAPAN KERANGKA MANAJEMEN RISIKO KLINIS DALAM PRAKTIK KEBIDANAN, MENCAKUP IDENTIFIKASI RISIKO YANG SPESIFIK - Sefentina Sefentina; Santi Widya Purba; May Linda Kristina (Jurnal Minfo Polgan, 2022)
Midwifery practice, although focused on physiological events, is not free from clinical risks that have the potential to cause injury or harm to mothers and babies. Incidents such as postpartum hemorrhage, neonatal asphyxia, or infection can have serious consequences. Clinical risk management is a systematic approach to identifying, assessing, and mitigating potential hazards in healthcare to improve patient safety. This literature review aims to explore the application of a clinical risk management framework in midwifery practice, encompassing specific risk identification, risk assessment methods, and effective mitigation strategies. The review results indicate that proactive integration of clinical risk management can reduce adverse incidents, increase adherence to clinical standards, improve team communication, and ultimately, improve maternal and infant health outcomes. Implementation challenges include a lack of a reporting culture, limited resources, and the need for ongoing training. Comprehensive implementation requires leadership commitment and the active participation of all midwifery staff.